How is Location Measured in Housing Valuation? A Systematic Review of Accessibility Specifications in Hedonic Price Models - Axel Viktor Heyman; Stephen Law; Meta Berghauser Pont (Urban Science, 2018)
Accessibility is frequently used for measuring location in housing studies, but specifications of the measures differ greatly and its implications are hardly discussed. This paper sets out to systematically review accessibility measures that are used in hedonic price models (HPM), a method for estimating the implicit value of housing characteristics, such as location. From a systematic database search of peer-reviewed journal articles, we examined 54 articles that applies accessibility measures in hedonic price models that are based on three aspects of measure specification: type, impedance, and opportunities. We find that there are clear couplings between different impedances, types, and opportunities. We also noticed a tendency towards less advanced measurements, such as Euclidean distance and zonal measures, being used. Furthermore, we argue that these basic measures have a weaker connection to consumer perception, which is fundamental to the hedonic price approach. We also observed a lack of consideration to how this coupling between type, impedance, and opportunity could possibly affect the results. Theoretically, we can already conclude that some dominating impedances poorly relate to the fundamental theories of HPM, but this also points to the need for further research to empirically test the influence of the type-impedance-opportunity specification on the price estimates in HPM.